Comparing Best Practice Public Service Innovation in East Java: Type, Distribution, and Consequences - M. Rizki Pratama; Alfin Maharani Rosidah; Salwa Kusumaningtyas (Journal of Governance, 2023)
Abstract: The Public Service Innovation Competition (KIPP) organized by the Kemenpan-RB has yielded numerous award-winning innovations since its inception in 2014. The competition attracts participation from government agencies at the national, local, and village levels. In particular, local governments in East Java have consistently produced the majority of winners in the Top 99 public service innovations category, partly due to the abundance of capable Regional Heads in the region who foster innovation. Given their superior performance, it is pertinent to assess the extent to which innovation has been adopted in East Java since 2014. Therefore, this study aims to investigate the type, distribution, and impact of public service innovation across all local governments in East Java. The researcher utilized best practices research methodology and analyzed the Kemenpan-RB's top 99 report documents on public service innovation. The findings reveal that there has been substantial progress in the development of public service innovation in East Java, with the Regency Government being the leading innovator. Moreover, innovation has been integrated into the core mission of local governments across East Java. However, there is a need for local governments at all levels to adopt digital innovation and engage in collaborative problem-solving with other institutions to meet the evolving needs of the public.